A new pyranoxanthone from Calophyllum soulattri - Mah, Siau Hui; Ee, Gwendoline Cheng Lian; Rahmani, Mawardi; Yap, Taufiq Yun Hin; Md. Sukari, Mohd Aspollah; Teh, Soek Sin (MDPI, 2011)
Our interest on xanthones from the Calophyllum genus has led us to a detailed study on the chemistry of the stem bark of Calophyllum soulattri. This gave one new pyranoxanthone, soulattrin (1), together with three other xanthones, caloxanthone B (2), caloxanthone C (3), macluraxanthone (4), the triterpene friedelin (5) and the steroid stigmasterol (6). The identities of these compounds were established using analyses of 1D and 2D NMR data.